EFFECT OF OXIDATIVE STRESS ON LIPID PROFILE AND BLOOD PARAMETERS TO A SAMPLE OF STUDENTS AT UNIVERSITY OF ZAKHO DURING EXAMES - Mohammad Ahmad Hamza; Imad Taher Abdulla; Enaam Ahmed Hamza (Tikrit Journal of Pure Science, 2018)
Worry, anxiety through Study and preparative to exam may lead to mental stress. Mental stress may contribute to oxidative stress in the body which is the change in balance between oxidants and antioxidants.